Extracellular vesicles participate in the pathogenesis of sepsis - Tian, Chang; Wang, Ke; Zhao, Min; Cong, Shan; Di, Xin; Li, Ranwei (Frontiers in Cellular and Infection Microbiology, 2022)
Sepsis is one of the leading causes of mortality worldwide and is defined as life-threatening organ dysfunction caused by a dysregulated host response to infection. The early diagnosis and effective treatment of sepsis still face challenges due to its rapid progression, dynamic changes, and strong heterogeneity among different individuals. To develop novel strategies to control sepsis, a better understanding of the complex mechanisms of sepsis is vital. Extracellular vesicles (EVs) are membrane vesicles released from cells through different mechanisms. In disease states, the number and cargoes of EVs produced by activated or apoptotic cells are altered, regulating the function of local or distant host cells through autocrine or paracrine. Current studies have found that EVs are involved in the occurrence and development of sepsis through multiple pathways. In this review, we focus on changes in the cargoes of EVs in sepsis, the regulatory roles of EVs derived from host cells and bacteria, and how EVs are involved in multiple pathological processes and organ dysfunction in sepsis. Overall, EVs have great application prospects in sepsis, such as early diagnosis of sepsis, dynamic monitoring of disease, precise therapeutic targets, and prevention of sepsis as a vaccine platform.